Exergy of Asphalt Concrete Mix - V. N. Romaniuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2003)
Determination of material exergy in a flow has been studied for asphalt concrete mix. Methodology for calculation of concentration component of asphalt concrete mix exergy has been proposed in the paper.